Contrasting Effects of Leadership Style and Work Communication on Employee Performance: The Mediating Role of Job Satisfaction - Lince Wulandari; Azwardi; Wita Farla WK (International Journal of Economics Accounting and Management, 2026)
Employee performance in public organizations remains a critical issue, particularly when leadership practices and workplace communication are not fully effective in supporting organizational goals. This study aims to examine the effects of leadership style and work communication on employee performance, with job satisfaction serving as an intervening variable. The study was conducted among 147 employees of a local government institution using a quantitative approach. Data were collected through questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0. The findings reveal that work communication has a positive and significant effect on employee performance, whereas leadership style has a significant but negative effect on performance. In addition, leadership style and work communication significantly influence job satisfaction, and job satisfaction significantly affects employee performance. Furthermore, job satisfaction mediates the relationships between leadership style and employee performance as well as between work communication and employee performance. The study concludes that effective work communication and enhanced job satisfaction are key factors in improving employee performance, while leadership practices require further adjustment to better support organizational outcomes